Wnt signaling in human and mouse breast cancer: Focusing on Wnt ligands, receptors and antagonists. Issue 11 (19th September 2018) - Yin, Ping; Wang, Wei; Zhang, Zhongbo; Bai, Yu; Gao, Jian; Zhao, Chenghai
Abstract : Wnt proteins, a group of secreted glycoproteins, mainly combine with receptors Frizzled (FZD) and/or low‐density‐lipoprotein receptor‐related proteins 5/6 (LRP5/6), initiating β‐catenin‐dependent and ‐independent signaling pathways. These pathways, which can be regulated by some secreted antagonists such as secreted Frizzled‐related proteins (SFRP) and dickkopf‐related protein (DKK), play a critical role in embryo development and adult homeostasis. Overactivation of Wnt signaling has been implicated in some human diseases including cancer. Wnt transgenic mice provide convincing evidence that Wnt signaling is involved in breast cancer initiation and progression, which is further strengthened by observations on human clinical breast cancer patients and studies on in vitro cultured human breast cancer cells. This review focuses on the roles of Wnt ligands, receptors and antagonists in breast cancer development instead of molecules or signaling transactivating β‐catenin independent on Wnt upstream components. Abstract : Studies from Wnt transgenic mice and observations on human clinical patients indicate that Wnt upstream components contribute to the generation of tumor‐initiating cells and metastasis‐initiating cells, thereby inducing breast carcinogenesis and promoting breast metastasis, especially in basal‐like/triple‐negative breast cancers.